Supine Ultrasound-guided Percutaneous Nephrolithotomy with Retrograde Semi-rigid Ureteroscopic guidwire retrieval: Description of an Evolved Technique - Khazaali, Mahziar; Khazaeli, Dinyar; Moombeini, Hayat; Jafari-Samim, Jamal (Urology Journal, 2017)
Purpose: Ultrasound-guided PCNL in Galdakao-modified supine Valdivia (GMSV) position has taken into consideration during the last decade; however, guidewire slippage during tract dilatation is still a big concern in this approach. Here we presented our results of combination of this modification with ureteroscopic guidewire retrieval to ensure a safe and confident renal access. Materials and Methods: From June 2015 to March 2016, 30 consecutive patients with renal stone of ? 2.5 cm were enrolled. After general anesthesia, all patients were positioned in GMSV position. Semi-rigid ureteroscopy up to the renal pelvis was performed by an assistant urologist. Ultrasound (US)-guided renal access and passage of guidewire was performed by another urologist after which the first urologist grasped and retrieved the guidewire from the renal pelvis to the ureter and then out of urethra. Stone manipulation was performed as standard PCNL. All patients were evaluated regarding age, stone burden, anthropometrics measurements, major and minor surgical complications, and stone free rate. Result: Guidewire retrieval was successful in 26 patients (86.7%) and tract dilatation was achieved in all (100%) of this group. In other 4 patients (13.3%) retrograde endoscopic guide wire retrieval failed; in one patient, (3.33%) ureteroscope did not reach the renal pelvis because of tall stature; One patient (3.33%) had narrow calyceal infundibulum which prevented the guidwire passage along the stone to reach to the renal pelvis, and for two patients (6.67%) ureteroscope did not pass the ureteropelvic junction because of narrow ureteropelvic angle. Conclusion: Guidewire retrieval seems to improve the results of US-guided GMSV position PCNL by eliminating the possibility of guidewire slippage during tract dilatation.